Everything you need to ace pre-algebra & algebra 1 in one big fat notebook : the complete high school study guide - Wang, Jason (Mathematics educator) (Big fat notebook., 2021)
"The Big Fat Notebook series for high school takes on Pre-Algebra & Algebra I, often a student's first high school-level math course, and a big challenge"--